Determination of the Heartbeat of Large-Horn Cattle - Makhsetbaevich, Kaljanov Damir; Bisenbaevna, Jienbaeva Myrigul (American Journal of Biology and Natural Sciences, 2024)
Heart rate detection in cattle is a critical parameter for monitoring health, stress levels, and overall well-being, especially in modern livestock management and veterinary practices. This study explores advanced methodologies for accurate heart rate measurement in cattle using non-invasive techniques, such as wearable sensors, photoplethysmography (PPG), and infrared thermography. The findings highlight the importance of integrating technology to enhance real-time health monitoring, reduce stress during data collection, and improve disease detection and management. The study demonstrates that wearable sensors provide reliable data in varying environmental conditions, offering a practical solution for farmers and veterinarians. This research underscores the potential for smart technology to revolutionize cattle health monitoring by providing accurate, continuous, and stress-free heart rate measurement.